El femtoscopio puede ser implementado utilizando dispersión de electrones y rayos X de bajas energías - Jiménez, Edward Henry (2018)
Femtoscope involves the discernment and di erentiation of each element in atom and molecule, this logically implies measurement of the radius, never the exact position of protons, neutrons, nucleus and electrons. is work increases the level of precision in the atomic and nuclear measurements of the nanometers, characteristic of the atom to the order of femtometers, characteristic of nucleons.Using the concepts of resonance and Schrödinger equation, the interaction of electrons and low energy photons with the matter is studied, and the atomic and nuclear radius are measured for elements of periodic table. We worked with the NIST public data and GC/MS chromatography information of the FIQ-UCE.In synthesis, the resonance of x-rays at low energies (<70 keV) gives the atomic and nuclear geometry of the K-layer. Whereas, the resonance of electrons at low energies (<2 keV) gives the energies of outer layers of electron and the average radius of atom.